Working Capital Management in Modern Rice Milling Firms at Kangayam, Tamil Nadu - Selvanayaki, S.; Sivakumar, S. D.; Mahendran, K. (Indian Journal of Finance, 2015)
This study was conducted to evaluate the working capital management practices adopted by the rice milling firms and to analyze its impact on profitability. Primary data on working capital management practices were collected by using an interview schedule, and the financial data were obtained from the records maintained by the firms. The study involved assessment of the working capital management practices adopted by the rice milling firms in terms of raw material ordering system and frequencies of overstocking of inventory. Working capital management efficiency indices, namely performance index, utilization index, and efficiency index were computed from the financial data, and it was found that the efficiency index was more than one during the study period, indicating an efficient working capital management by the firms. The average CCC of the firms during the study period was 3 months, and DPO had a significant and positive relationship with profitability of the firms.